Aortic valve surgery for aortic regurgitation caused by Libman-Sacks endocarditis in a patient with primary antiphospholipid syndrome: a case report - Ho, Y. L.; Zaidi, Nurul A.; Salleh, Ahmadi; Kareem, Basheer A. (International Surgery Journal, 2021)
Antiphospholipid syndrome is an antibody mediated pro-thrombotic state leading to various arterial and venous thromboses. The syndrome can be either primary or secondary to other autoimmune diseases. Cardiac involvement, in particular valvular disease is common in patients with antiphospholipid syndrome (APS) but it is frequently underestimated as most clinicians do not routinely screen for valvular lesion in patients with APS unless they are symptomatic. Valvular disease associated with antiphospholipid syndrome often occurs as valve thickening and non-bacterial vegetation or Libman-Sacks endocarditis, with a higher propensity towards mitral valve although haemodynamically significant valvular dysfunction is rare. Valve surgery in patients with APS carries considerable early and late morbidity and mortality, usually caused by thromboembolic and bleeding events. The perioperative anticoagulation management and haemostatic aspect of APS present exceptional challenges to clinicians, surgeons, anaesthetists and laboratory personnel. Thus, the indication of valve surgery and the choice of valve remains a critical consideration in these patients. We present a successful isolated aortic valve replacement with cardiopulmonary bypass in a 48 year old lady with newly diagnosed antiphospholipid syndrome, who has severe aortic regurgitation as a result of Libman-Sacks endocarditis. Antiphospholipid antibodies were positive and the clinical data showed both negative cultures and infective parameters. Surgically resected vegetations revealed sterile fibrin fibrinous and verrucous vegetations on aortic valve. Valve replacement and the course of cardiopulmonary bypass were uneventful, and patient was discharged well.